Human helicase RECQL4 drives cisplatin resistance in gastric cancer by activating an AKT-YB1-MDR1 signaling pathway - Mo, Dongliang; Fang, Hongbo; Niu, Kaifeng; Liu, Jing; Wu, Meng; Li, Shiyou; Zhu, Tienian; Aleskandarany, Mohammed A.; Arora, Arvind; Lobo, Dileep N.; Madhusudan, Srinivasan; Balajee, Adayabalam S.; et al. (American Association for Cancer Research, 2016)
Elevation of the DNA-unwinding helicase RECQL4, which participates in various DNA repair pathways, has been suggested to contribute to the pathogenicity of various human cancers, including gastric cancer. In this study, we addressed the prognostic and chemotherapeutic significance of RECQL4 in human gastric cancer, which has yet to be determined. We observed significant increases in RECQL4 mRNA or protein in >70% of three independent sets of human gastric cancer specimens examined, relative to normal gastric tissues. Strikingly, high RECQL4 expression in primary tumors correlated well with poor survival and gastric cancer lines with high RECQL4 expression displayed increased resistance to cisplatin treatment. Mechanistic investigations revealed a novel role for RECQL4 in transcriptional regulation of the multidrug resistance gene MDR1, through a physical interaction with the transcription factor YB1. Notably, ectopic expression of RECQL4 in cisplatin-sensitive gastric cancer cells with low endogenous RECQL4 was sufficient to render them resistant to cisplatin, in a manner associated with YB1 elevation and MDR1 activation. Conversely, RECQL4 silencing in cisplatin-resistant gastric cancer cells with high endogenous RECQL4 suppressed YB1 phosphorylation, reduced MDR1 expression, and resensitized cells to cisplatin. In establishing RECQL4 as a critical mediator of cisplatin resistance in gastric cancer cells, our findings provide a therapeutic rationale to target RECQL4 or the downstream AKT-YB1-MDR1 axis to improve gastric cancer treatment.